Voltage-Gated Sodium Channels: Biophysics, Pharmacology, and Related Channelopathies - Savio Galimberti, Eleonora; Gollob, Michael; Darbar, Dawood (Frontiers in Pharmacology, 2012)
Voltage-gated sodium channels (VGSC) are multi-molecular protein complexes expressed in both excitable and non-excitable cells. They are primarily formed by a pore-forming multi-spanning integral membrane glycoprotein (α-subunit) that can be associated with one or more regulatory β-subunits. The latter are single-span integral membrane proteins that modulate the sodium current (INa) and can also function as cell-adhesion molecules (CAMs). In-vitro some of the cell-adhesive functions of the β-subunits may play important physiological roles independently of the α-subunits. Other endogenous regulatory proteins named “channel partners” or “channel interacting proteins” (ChiPs) like caveolin-3 and calmodulin/calmodulin kinase II (CaMKII) can also interact and modulate the expression and/or function of VGSC. In addition to their physiological roles in cell excitability and cell adhesion, VGSC are the site of action of toxins (like tetrodotoxin and saxitoxin), and pharmacologic agents (like antiarrhythmic drugs, local anesthetics, antiepileptic drugs, and newly developed analgesics). Mutations in genes that encode α- and/or β-subunits as well as the ChiPs can affect the structure and biophysical properties of VGSC, leading to the development of diseases termed sodium “channelopathies”. This review will outline the structure, function and biophysical properties of VGSC as well as their pharmacology and associated channelopathies and highlight some of the recent advances in this field